Outcome of antiretroviral therapy: a longitudinal study in Nalgonda district, Telangana - Gorantla, Misha; Malhotra, Varun M.; Nagaraj, Kondagunta (International Journal Of Community Medicine And Public Health, 2018)
Background: India is among the list of countries with highest HIV prevalence. Retention in care is vital to maintain good health and obtain antiretroviral therapy (ART) medicines on time. The objectives of the study were to study the clinico-demographic profile of study population and to study the outcome of ART after one year of treatment initiation. Methods: This is an observational follow up (longitudinal) study done on 142 patients which included all newly diagnosed (diagnosed on or after 1st January 2012), sero positive, adult patients, enrolled at an ART centre and started on treatment during the months of December 2012, January 2013, February 2013, using a pre-designed, pre-tested questionnaire. They were visited again a year after ART initiation and outcome was assessed along with determinants of poor outcome. Results: Mortality at the end of one year was 9.15%, rate of loss to follow up (LFU) was 7.6%.Therefore a total of 73.2% cases were retained in care and 26.8% were disengaged from care (LFU and dead) after one year of ART initiation. Risk factors found to have significant association with being disengaged from care were male sex, unmarried/widowed/divorced/separated individuals, lower socio economic status, illiteracy, unskilled occupation, spouse status negative for HIV, presence of addictions like alcoholism, smoking, experience of drug side effects, early WHO clinical stage, presence of opportunistic infections and low CD4 counts. Conclusions: Many of the risk factors are amenable for intervention and may be incorporated to strengthen the programme.